A Systematic Review on Chemo-entrepreneurship - Mohammad Agus Prayitno; Sri Haryani; Sri Wardani; Nanik Wijayati; Sutikno Sutikno; Dyah Rini Indriyanti; Ellianawati Ellianawati (International Conference on Science, Education, and Technology, 2022)
Written briefly in English in one paragraph of 150-250 words, containing background, research objectives, methodology, results & important findings of the study. The purpose of this study is to determine research trends related to Chemo-entrepreneurship, which is beneficial in developing learning models that are in line with the independent learning curriculum. This study is a systematic literature review of Chemo-entrepreneurship from 47 articles indexed by Scopus and Google Scholar published between 2010 – 2022. The findings show that the area where Chemo-entrepreneurship is researched the most is the city of Semarang. The most widely used material in Chemo-entrepreneurship research is colloids. The most common type of research related to Chemo-entrepreneurship is development research. Research related to Chemo-entrepreneurship is mostly done at the Senior High School. The journal that publishes the most articles on Chemo-entrepreneurship is the innovative journal of science education. Most of the research institutions that conduct research on Chemo-entrepreneurship are from Semarang State University. There is no research on Chemo-entrepreneurship associated with 21st century skills, Chemo-entrepreneurship-Education for Sustainable Development (ESD), Chemo-entrepreneurship-environmental education, Chemo-entrepreneurship-STEM, and Chemo-entrepreneurship-green deal. From several analyzes in this literature review, we suggest analyzing topics that are still rarely studied for further study.